Uptake and attitudes regarding hepatitis A vaccine among childcare centre staff, administrators, and parents. (January 2017) - Rebmann, T.; Baskin, C.R.; Loux, T.M.; Wakefield, M.
Abstract: Objectives: Study objectives were to assess parents' and childcare agency staff's uptake of and attitudes/beliefs related to hepatitis A vaccine. Study design: Cross-sectional survey. Methods: Questionnaires were administered to parents and staff in 23 St. Louis childcare agencies between September and December 2014. Categorical data were compared using Chi-squared test. Multivariate logistic regression, stratified by staff vs parents, was used to find predictors of hepatitis A vaccine uptake. Results: In total, 351 staff and parents participated (response rate = 32%). More staff than parents had been offered or recommended to receive hepatitis A vaccine by a healthcare provider (55.4% vs 36.6% and 53.3% vs 28.7%, respectively; P  = .001 for both). More staff than parents received hepatitis A vaccine (85.3% vs 67.5%, Chi-squared test = 11.0, P  < .001). Predictors of staff vaccine uptake included being aware of CDC vaccination recommendations (OR = 11.2, CI = [1.4–91], P  < .05), employer recommendation to get vaccinated (OR = 8.1, CI = [1.8–36.8], P  < .01), and having a mandatory staff vaccination policy (OR = 4.8, CI = [1.2–19.7], P  < .05). Predictors of parent vaccine uptake included being offered the vaccine by a healthcare provider (OR = 4.3, CI = [1.3–4.9], P  < .001), being aware of the CDC vaccination recommendations (OR = 4.0, CI = [2.0–8.0], P  < .001), and having received influenza vaccine previously (OR = 2.5, CI = [1.3–4.9], P  < .01). Conclusion: In this study population, many childcare agency staff and parents have received hepatitis A vaccine, though staff immunization rates are at the minimum needed to reach herd immunity levels. Having employers encourage vaccination, offer free vaccine, or make vaccine available onsite could increase staff vaccination rates. Public health should partner with childcare agencies to increase staff vaccine uptake, which could result in community herd immunity. Highlights: Childcare staff are at increased risk of hepatitis A, yet little is known about their uptake of hepatitis A vaccine. More childcare staff than parents had received hepatitis A vaccine, and their predictors for vaccine uptake differed. Staff vaccination predictors included awareness of recommendations, employer recommendation, and having a mandatory policy. Parent vaccination predictors included healthcare provider offer, awareness of recommendations, and previous vaccination.